2015
DOI: 10.3892/ol.2015.3985
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial solitary fibrous tumors: A report of two cases and a review of the literature

Abstract: Abstract. Solitary fibrous tumors (SFTs) are uncommon, with the pleura as a site of predilection. Central nervous system SFTs, particularly intracranial SFTs, are extremely rare. The lesions are generally benign and localized, and surgery is the main therapeutic solution. The current study reports the cases of a patient who presented with right haunch pain, right leg weakness and paresthesias for several months, and a patient with a history of unexpected loss of consciousness. Magnetic resonance imaging reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The tumour is further characterised by a positive CD34 stain and a positive STAT-6 stain [ 4 6 ]. Some authors also reported positive bcl-2 and vimentin staining in ISFTs [ 6 7 ]. Dedifferentiated SFT may be positive for p53, while the conventional, fibrous component is usually negative or shows scarcely scattered positive staining [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tumour is further characterised by a positive CD34 stain and a positive STAT-6 stain [ 4 6 ]. Some authors also reported positive bcl-2 and vimentin staining in ISFTs [ 6 7 ]. Dedifferentiated SFT may be positive for p53, while the conventional, fibrous component is usually negative or shows scarcely scattered positive staining [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…At MRI, a majority of cases are homogeneous on T1-weighted imaging (most often isointense). In literature, the most common presentation is a heterogeneous pattern on T2-weighted imaging with hypointense areas [ 1 7 ]. This may be explained by the existence of two separate components within the tumour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrence of intracranial SFTs and other tumor types is particularly rare, and SFTs are easily misdiagnosed due to a lack of typical symptoms and imaging features. By contrast, meningiomas, which arise from cells covering the arachnoid layer of the dura mater or from the intraventricular choroid plexus, present with a typical dural tail sign upon magnetic resonance imaging (MRI) ( 2 , 3 ). Histologically, both meningiomas and SFTs are composed of interlacing fascicles of spindle or ovoid tumor cells with intervening collagen bands.…”
Section: Introductionmentioning
confidence: 99%
“…Its damage could be caused by compression on the adjacent structures or increased intracranial pressure. [4]…”
mentioning
confidence: 99%